Blockchain-based verification and authentication system for secure online communications - Lam, Jeslyn Xin Yi (Nanyang Technological University, 2023)
The increase in cybercrime and scams, particularly among young adults, has resulted in a pressing need for improved communication security. This project proposes a blockchain-based verification and authentication system that uses smart contracts to manage a dynamic pool of approved and cautioned identities. By verifying and authenticating communication attempts, such as calls and messages, the system provides a safe online space for users to interact without the fear of potential adversarial attacks.